Comparative Antidepressant, Anxiolytic, and Acute Toxicity Evaluation of Lemon Peel and Peppermint Leaves Extracts in Mice - Neli Syahida Ni'ma; Annisa Aulia Savitri; Dyah Mahendrasari Sukendra; Ronny Meilano Hardiansyah; Ika Ayu Puspaningtias; Gavriel Fauzan Fathurahman; Septia Linasari (Biology, Medicine, & Natural Product Chemistry, 2025)
Depression and anxiety are prevalent psychiatric disorders, and current treatments are often limited by side effects, delayed onset, and resistance. Natural products are being explored as safer alternatives, and lemon peel (Citrus limon) and peppermint leaves (Mentha × piperita L.) contain diverse bioactive compounds with neuroprotective potential. This study evaluated the antidepressant and anxiolytic effects of their ethanolic extracts, individually and in combination, in male Swiss Webster mice. Phytochemical screening confirmed the presence of alkaloids, flavonoids, phenols, tannins, saponins, and steroids in both extracts. Antidepressant activity, assessed by the Forced Swimming Test (FST) and Tail Suspension Test (TST), showed that both extracts and their low-dose combination significantly reduced immobility time, with effects comparable to fluoxetine. In contrast, the high-dose combination did not enhance efficacy. Anxiolytic activity, evaluated using the Elevated Plus Maze (EPM) and Light-Dark Box (LDB), revealed that peppermint extract exerted the strongest effect, followed by the low-dose combination and lemon peel. Acute oral toxicity testing at 2000 mg/kg showed no mortality or adverse effects. These findings suggest that lemon peel and peppermint extracts possess antidepressant and anxiolytic properties with favorable safety profiles, supporting their potential as natural alternatives or adjuncts for managing mood disorders.